Counseling individuals with life-threatening illness - Doka, Kenneth J. (Springer Pub. Company, 2014)
""With characteristic clarity, Doka draws on the classic and contemporary literature as well as his own pedagogy and practice in death and dying to offer orienting concepts for the whole spectrum of care people may require when illness intrudes into their lives. For each phase of the illness trajectory ... he offers intelligent attention to the problems and prospects people confront, and in countless examples of actual clinical situations he brings to life the concepts that inform compassionate care."". From the Foreword by Robert A. Neimeyer, PhD. University of Memphis. This holistic, family-c.